{N′-[(E)-1-(5-Bromo-2-oxidophenyl)ethylidene]-4-hydroxybenzohydrazidato}pyridinecopper(II) - Zhang, Jian-Min (International Union of Crystallography, 2011)
In the title complex, [Cu(C(15)H(11)BrN(2)O(3))(C(5)H(5)N)], the central Cu(II) atom is in a square-planar CuN(2)O(2) coordination environment formed by the tridentate hydrazone and the monodentate pyridine ligands with N atoms in a trans-arrangement about the Cu(II) atom.